Degressive proportionality - source, findings and discussion of the Cambridge Compromise - Dniestrzański, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The principle of degressive proportionality in relation to the division of indivisible goods in the past few years – especially since the signing of the Treaty of Lisbon – has been one of the topics frequently appearing in studies of economists, mathematicians, lawyers and people involved in politics. It combines a purely theoretical and easily definable question with a very important practical problem that concerns primarily members of the European Union and countries aspiring to become one. The article shall include a debate and discussion of the findings of the Cambridge Compromise concerning proposals to solve the problem of allocating seats in the European Parliament.
Mathematical Economics, 2011, Nr 7 (14), s. 39-50
Keywords: degressive proportionality; European Parliament; Cambridge Compromise; Treaty of Lisbon